In silico and in vitro studies of fungicidal nature of lipopeptide (Iturin A) from Bacillus amyloliquefaciens RHNK 22 and its plant growth promoting traits - J. PARAMESHWAR, MOHAMED YAHYA KHAN, JAYASIMHA RAYULU; BEE HAMEEDA*, P. NARENDRAKUMAR, L. NAGESHWAR (Indian Phytopathology, 2016)
Phytopathogens cause several diseases in plants and reduce the crop yield. Biological control has emerged as alternatives to control of phytopathogenic fungi for sustainable agriculture. An in silico and in vitro studies of interaction of iturin A from Bacillus amyloliquefaciens RHNK 22 against fungal lectin of Macrophomina phaseolina was carried out. In silico study revealed that the iturin A binds on the outer surface of the lectin by interacting with three amino acids (TYR09, ARG7, and ASP 37) at a distance of 3Ã… and has an overall free energy of binding of -333.45K.cal/mol. The results of in vitro studies confirmed that the iturin A has fungicidal activity. Besides the production of iturin A, Bacillus amyloliquefaciens RHNK 22 showed production of indole acetic acid, ammonia, phytase and phosphate solubilisation and improved seed vigour index of maize using paper towel technique.